2022
DOI: 10.3389/fenvs.2022.891195
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Various Phytoconstituents in Tomato Seedling Growth and Meloidogyne incognita–Induced Stress Alleviation By Vermicompost Application

Abstract: In addition to chemical pesticides and fertilizers, the use of vermicompost can help in the management of root-knot nematodes (RKN) while also augmenting plant growth. The present study is carried out to determine the role of neem-based vermicompost on plant growth during stress produced by Meloidogyne incognita. Vermicompost (Vcom) and soil were mixed in various proportions (0, 20, 40, 60, 80, and 100%) and used to treat tomato plants against nematode infestation. After 10 days of inoculation of second-stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…In this research, proline levels were shown to appear significantly higher in nematode-infected plants. Consistent with the research conducted by Tikoria et al [ 58 ] and Khajuria and Ohri [ 63 ], we also recorded that the proline level increased considerably after the nematode invasion of the tomato plants.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this research, proline levels were shown to appear significantly higher in nematode-infected plants. Consistent with the research conducted by Tikoria et al [ 58 ] and Khajuria and Ohri [ 63 ], we also recorded that the proline level increased considerably after the nematode invasion of the tomato plants.…”
Section: Discussionsupporting
confidence: 92%
“…The findings derived from the current investigation additionally revealed a significant reduction in chlorophyll contents in tomato plants infected with M. enterolobii . In a previous study, the nematode infections in tomato plants reduced or altered photosynthetic pigments in tomato plants [ 58 ]. Chen et al [ 59 ] also determined that the leaf chlorophyll content of rice plants decreased after infection with M. graminicola , with an inoculum density ranging from 500 to 2000 J2s per plant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, enhanced activities of POD, CAT, and APX were observed in Vicia faba leaves infected with bean yellow mosaic virus, indicating that the ROS-scavenging systems may play an important role in managing the ROS generated in response to pathogens [ 82 ]. In the same context, Tikoria et al [ 93 ] demonstrated that protein content and enzyme activities of CAT, POD, APX, and PPO were shown to be reduced after nematode infestation but enhanced by vermicompost amendment, which played the same role as our BCAs treatments.…”
Section: Discussionmentioning
confidence: 65%
“…However, due to the complex factors affecting soil spectra, especially in-situ spectra collected in the field, early work focused on indoor spectra under controlled conditions [19]. However, predicting soil properties directly based on in-situ spectra in the field can save more time and cost [20]. The application of in-situ spectroscopy in the field is imminent [21].…”
Section: Background and Motivationmentioning
confidence: 99%